The Effect of the Numbered Heads Together (NHT) Cooperative Learning Model on Class VII Social Studies Learning Outcomes of SMP Negeri 5 Pematang Siantar T.A 2022/2023 - Clara Chyntia Harianja; Benjamin Albert Simamora; Binsar Tison Gultom (Indonesian Journal of Advanced Research, 2023)
This study aims to look at differences in learning outcomes for class VII students of SMP Negeri 5 Pematang Siantar using the Numbered Heads Together (NHT) Koopetarof learning model from the conventional learning model. From the test results it can be stated that the quality of the questions is good because the instrument is valid where the lowest validity is 0.36 (low validity) and the highest validity is 0.53 (sufficient validity), using the product moment formula. From the results of the study, it was found that the results of the normality test with the Liliefors test found that the data on the results of the two groups were normally distributed. From the results of the class homogeneous test, it has a homogeneous variance with 0.010 > 0.05 with a = 0.01 so that Ho is rejected. From the results of the analysis of the data obtained, it is known that (1) learning outcomes using cooperative learning type numbered heads together with X̅83.87, (2) learning outcomes with conventional learning with X̅75.03. Thus it can be concluded that (1) there are differences in student learning outcomes using cooperative learning type numbered heads together with conventional learning, (2) learning outcomes using cooperative learning type numbered heads together are better than learning outcomes using conventional learning. It can be seen from the results of the average test score of students with cooperative learning type numbered heads together is higher than the average test score of students with conventional learning.